The White Company - Doyle, Arthur Conan (Saga Egmont, 2022)
“...[W]orth a hundred Sherlock Holmes stories.” That was how Arthur Conan Doyle characterized The White Company, the book he considered his best work. Set against the background of the Hundred Years War, an extended conflict between France and England, The White Company rivals the best works of historical romance. Not only is it richly textured with accurate historical detail, it features several memorable characters: Sir Nigel Loring and Alleyne, his squire, as well as Hordle John, a lovable rogue, and Allewyn, the master archer.